School health education nowadays : challenges and trends - Carvalho, Graça Simões de (2012)
School health education has been viewed in a large variety of perspectives. In this chapter we present, in a historic approach, the biomedical model, the holistic view as well as the health promotion, autonomy and citizenship perspectives of health education. The aims of the health promoting school and the relevance of partnerships with the health sector, the pupils, their families and the community in health education are emphasised. Social representations, ethics and values in health education are referred. Special attention is given to models of school health education, the nature of knowledge in health education, prevention of health risks, effectiveness of health education practices and also to teachers’ practices and their role and training in health education.